Towards Excellence in Higher Education –The Experience of Open University Malaysia (OUM) - Chiam , Chooi Chea; Lim, Tick-Meng; Norbaini Abdul Halim; Nur Azlin Omar (2011)

(untitled)
With the advancement in communication technology via the Internet and World Wide Web, attention has been drawn to Open Distance Learning (ODL) as an alternative mode for teaching and learning. In Malaysia, OUM is well acknowledged as the pioneer for ODL education. OUM has placed great effort in leveraging ICT aimed at making higher education more accessible and affordable across the country. This paper will discuss how OUM has contributed towards the democratisation of higher education in Malaysia. The paper will also examine OUM’s delivery of online teaching and learning using the My Virtual Learning Environment (MyVLE).